The Influence of Information Technology, Leadership Style, and Collaboration on Clinic Income Levels, Mediated by Work Quality : (A Study at Ibumas Clinic, Tanjung Pinang) - Liud, Siumiany; Bayu Wahyudi; Yani Restiani Widjaja (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
The increasing need for efficient health service management encourages clinics to optimize organizational resources in order to improve financial performance. This study analyzes the influence of information technology, leadership style, and collaboration on clinic income with work quality acting as a mediating variable at Klinik Ibumas Tanjung Pinang. The research employed a quantitative explanatory approach using Structural Equation Modeling–Partial Least Square (SEM-PLS) with 70 respondents consisting of health workers and administrative staff selected through simple random sampling. The findings reveal that information technology, leadership style, and collaboration have a positive and significant effect on work quality, and these variables also positively influence clinic income. Work quality further demonstrates a significant effect on clinic income and mediates the relationship between information technology, leadership style, collaboration, and clinic income. These results imply that strengthening digital technology utilization, adaptive leadership practices, and effective interprofessional collaboration can enhance employee work quality and contribute to improved clinic financial performance.